Pendampingan Pelatihan Pelatihan Sulam Pita Untuk Meningkatkan Kreatifitas Keputrian Anggota PPI Sakarya Majlis Ta’lim Annisa Istanbul Turki - Ihsan, Nur Hadi; Syahruddin, Syahruddin; Huwaida, Jaziela; Salsabila, Raden Rara; Mahdiyah, Andi Nur Fadhila; Aini, Rihan Nurul; Sasongko, Yogi Banar (Universitas Pahlawan Tuanku Tambusai, 2025)
Community service activities through ribbon embroidery art training aim to increase creativity and soft skills, especially among members of the Indonesian Student Association (PPI) in Sakarya, Turkey. This training was carried out as part of the Real Work Lecture (KKN) program at Darussalam Gontor University to empower the community through developing practical skills. The art of ribbon embroidery, which has been known since the 17th century, was chosen as training material because of its creative and applicable nature. The training method involves lectures for basic introduction and hands-on practice to support participants' technical skills. This activity focuses on making simple motifs that are applied to media such as headscarves, thereby providing direct and relevant benefits for participants. The results of the activity showed that ribbon embroidery training was able to increase participants' understanding and skills in the field of handicraft arts. Apart from that, this training also motivates participants to continue to develop their creativity and skills in supporting PPI's women's activities. Thus, this program has a positive impact on community empowerment and strengthening soft skills, while preserving traditional arts that have high cultural value.